Comparison of the Muscle Activity of Lumbar Stabilizers Between Stoop and Semi-Squat Lifting Techniques at Different Lifting Loads - Yang, Hoe-Song; Kwon, Oh-Yun; Lee, Yeon-Seop (Han'guk Chŏnmun Mulli Ch'iryo Hakhoe chi = Journal of the Korean Academy of University Trained Physical Therapists, 2012)
This study was performed to compare the muscle activity of lumbar stabilizers between stoop and semi-squat lifting techniques at different lifting loads. Twenty healthy subjects (9 males, 11 females) were recruited for this study. Muscle activity of external obliques (EO), internal obliques (IO) and lumbar multifidus (LM) muscle was measured by surface electromyography during stoop and semi-squat lifting at different lifting loads (10%, 20%, and 30% of the subject’s body weight). A one-way repeated measure ANOVA was applied. The results showed that EMG activity of EO was significantly increased with a load of 30% of body weight compared to 10% and 20% of body weight in both lifting techniques (p<.05). Muscle activity of LM was significantly increased in 20% compared to 10% and 30% compared to 10% of subject’s body weight in stoop lifting and the muscle activity of LM was significantly increased in 20% compared to 10%, 30% compared to 20%, and 30% compared to 10% of the subject’s body weight in semi-squat lifting (p<.05). However, there was no significant difference in activity of IO according to lifting loads in both lifting techniques. There were no significant differences in muscle activity of EO, IO, and LM between stoop and semi-squat technique (p>.05). Therefore, the results of this study suggested that the EO can contribute to increase the lumbar stability during stoop and semi-squat lifting at 30% of body weight rather than at lower loads, and the LM seems to act as counteractor to imposed loads during stoop and semi-squat lifting with increasing loads. KCI Citation Count: 0